Poor Families Empowerment through Provision of Stimulant Funds: A Team Based Project of Pejuang Muda in Sukabumi Regency - Halimah Halimah; Yeni Suryani; Asep Saepuloh (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The intention of this article is to report one of Pejuang Muda program called Team Based Project in the form of empowering a poor family. After going through the stages of observation, interviews, and distributing questionnaires on problems to all sub-districts in the Sukabumi Regency area, it was determined that the program to be implemented by the Pejuang Muda of Sukabumi Regency was a humanitarian program in the form of provision to be given to Mrs. Kokob and Mr. Eman, a person with disabilities. The Poor Families empowerment program was implemented on the 16th of December 2021 in Darussalam Village RT 8 RW 6 Bantargadung Regency Sukabumi Regency West Java. The result shows that 1) The target of this program can be achieved properly according to planning and expectations. 2) Through this program Ibu Kokob can run a stall so that she can earn money from it for helping their daily needs. 3) The team of Pejuang Muda of Sukabumi Regency succeeded in conducting the Team Based project as one of the programs of Pejuang Muda. They were able to find the problem, set the solution, and solve the problem that occurred in the society